(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
This research aims to evaluate the compliance management system in the general administration of Rashid bank according to the requirements of the international standard (ISO )37301:2021), and to determine the size of the gap between the actual reality and what it should be according to the requirements of that specification. The research problem was represented by raising the main question, which is (What is the level of evaluation of the compliance management system according to the requirements of the international standard (ISO 37301:2021) in the bank under study?) In order to achieve the objectives of the research, the researcher conducted a case study through personal interviews and field experience, in addition to holding a workshop with those concerned in the bank under study to benefit from the discussion and dialogue in including the paragraphs of the checklist for the specification, which is a main tool in collecting data for this research, which included (255) questions distributed over (26) twenty-six items and (7) seven requirements. A number of statistical methods were adopted to analyze the data, including (frequencies, percentages, weighted arithmetic mean), and the research resulted in a set of The most prominent results were: The level of actual application and documentation of the international standard specification was (51.35%), which is close to the weight of partially applied and fully documented, which means that the size of the gap reached (48.65%).